The living Barents Sea response to peak-warming and subsequent cooling - E. Eriksen; B. Husson; G. Skaret; R. B. Ingvaldsen; P. Dalpadado; E. Johannesen; L. L. Jørgensen; B. Bogstad; A. V. Dolgov; D. V. Prozorkevich; T. A. Prokhorova; A. A. Russkikh; et al. (Scientific Reports)
Abstract The Arctic warms nearly four times faster than the global average, with maximum warming in the Barents Sea. Concurrently, changes in species distribution in this productive and highly exploited sub-Arctic hotspot has been found. However, studies so far have mostly focused on the effect of gradual warming on single species or trophic groups. We assess changes in zooplankton, fish and zoobenthos assemblages (130 species in 23 groups) and found heterogeneous response to ongoing warming. Temporally constrained cluster analysis showed that the warming was not continuous over the study period 2005–2022 but occurred in three phases: an initial period (2005–2011) cooler than the average for the whole study period, followed by a very warm period (2012–2016) and finally a cooler period again (2017–2022). The biotic response was greatest in the areas of largest oceanographic changes: in the northwest, the biomass of biota increased in most groups, including Arctic fish species, whereas in the southeast, the biomass of several fish species declined, while that of jellyfish and invasive snow crab increased. New knowledge is useful for generating scenarios for ecosystem responses to climate change.